2022
DOI: 10.1007/s00018-022-04386-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusins: from mitochondria to fertility

Abstract: Germ cell formation and embryonic development require ATP synthesized by mitochondria. The dynamic system of the mitochondria, and in particular, the fusion of mitochondria, are essential for the generation of energy. Mitofusin1 and mitofusin2, the homologues of Fuzzy onions in yeast and Drosophila, are critical regulators of mitochondrial fusion in mammalian cells. Since their discovery mitofusins (Mfns) have been the source of significant interest as key influencers of mitochondrial dynamics, including membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 166 publications
0
12
0
Order By: Relevance
“…At the GV stage, mitochondria in the oocyte gradually accumulate in the perinuclear space to provide energy for nuclear rupture and spindle traction. Subsequently, mitochondria gradually distribute evenly throughout oocytes to maintain the basal metabolism level [ 21 , 43 , 44 ]. However, in Dguok – / – oocytes, the movement and distribution of mitochondria were aberrant; mitochondria were irregularly clustered around the nucleus and in the cytoplasm both before and after germinal vesicle breakdown ( Figure 5 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…At the GV stage, mitochondria in the oocyte gradually accumulate in the perinuclear space to provide energy for nuclear rupture and spindle traction. Subsequently, mitochondria gradually distribute evenly throughout oocytes to maintain the basal metabolism level [ 21 , 43 , 44 ]. However, in Dguok – / – oocytes, the movement and distribution of mitochondria were aberrant; mitochondria were irregularly clustered around the nucleus and in the cytoplasm both before and after germinal vesicle breakdown ( Figure 5 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…At the GV stage, mitochondria in the oocyte gradually accumulate in the perinuclear space to provide energy for nuclear rupture and spindle traction. Subsequently, mitochondria gradually distribute evenly throughout the oocytes to maintain the basal metabolism level (21, 42, 43). However, in Dguok -/- oocytes, the movement and distribution of mitochondria are abnormal: mitochondria were irregularly clustered around the nucleus and in the cytoplasm, both before and after the germinal vesicle breakdown (Fig 5D-E).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, even though BHBA damaged mitochondria, leading to dysfunction, we found that the ATP content was increased; this may be related to increased mitochondrial fusion. We acknowledge the view that activation of the apoptotic system can uncouple the mitochondrial electron transport chain and down-regulate the level of ATP production [ 68 ]. Yet, the observed increase in ATP may be related to the properties of BHBA as an energetic substance; however, this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%